Efficient approach to produce multi‐functional copolymers for effective DNA binding. (11th August 2016) - Ganivada, Mutyala Naidu; N, Vijayakameswara Rao; Kumar, Pawan; Bhattacharya, Sourav; Shunmugam, Raja
Abstract : Norbornene‐derived copolymer with side‐chain phosphonic acid and cationic motifs (NORP‐PHOS‐CAT copolymer) are synthesized using ring opening metathesis polymerization method. All the monomers and polymers are characterized very carefully using nuclear magnetic resonance, MASS, Fourier transform infrared spectroscopy, and gel permeation chromatography technique. Thermogravimetric analysis, Fourier transform infrared spectroscopy, and scanning electron microscope techniques are employed to confirm the anchoring of Fe3 O4 particles to the NORP‐PHOS‐CAT copolymer. Formation of nano‐aggregates from NORP‐PHOS‐CAT copolymer is first observed in dynamic light scattering, and later, it is confirmed as nano‐spheres by scanning electron microscope and transmission electron microscopy studies. Zeta‐potential values of nano‐spheres suggest that the cationic motifs are on the surface. The encapsulation of anionic dye methyl orange to the nanocarrier is analyzed through UV–Vis spectroscopy in aqueous medium. DNA binding nature of NORP‐PHOS‐CAT‐Fe copolymer is confirmed through the circular dichroism measurement and UV–Vis spectroscopy. To the best of our knowledge, this is the first report where the norbornene‐derived copolymers that are elegantly synthesized with both magnetic as well as cationic nature to demonstrate the effective encapsulation of dye into the nano‐spheres followed by its release. Copyright © 2016 John Wiley & Sons, Ltd.